Centrality dependence of charged particle production at large transverse momentum in Pb–Pb collisions at √ˢɴɴ =2.76 TeV - Abelev, B.; Adam, J.; Adamovã, D.; Adare, A.M.; Aggarwal, M.M.; Aglieri Rinella, G.A.; Agócs, A.G.; Agostinelli, A.; Aguilar Salazar, S.; Ahammed, Z.; Ahmad, N.; Ahmad Masoodi, A.; et al. (Elsevier, 2013)
The inclusive transverse momentum (Pᴛ) distributions of primary charged particles are measured in the pseudo-rapidity range |η| < 0.8 as a function of event centrality in Pb–Pb collisions at √ˢɴɴ = 2.76 TeV with ALICE at the LHC. The data are presented in the Pᴛ range 0.15 < Pᴛ < 50 GeV/c for nine centrality intervals from 70–80% to 0–5%. The results in Pb–Pb are presented in terms of the nuclear modification factor Rᴀᴀ using a pp reference spectrum measured at the same collision energy. We observe that the suppression of high-Pᴛ particles strongly depends on event centrality. The yield is most suppressed in central collisions (0–5%) with Rᴀᴀ ≈ 0.13 at Pᴛ = 6–7 GeV/c. Above Pᴛ =7 GeV/c, there is a significant rise in the nuclear modification factor, which reaches Rᴀᴀ ≈ 0.4 for Pᴛ > 30 GeV/c. In peripheral collisions (70–80%), only moderate suppression (Rᴀᴀ = 0.6–0.7) and a weak Pᴛ dependence is observed. The measured nuclear modification factors are compared to other measurements and model calculations.
Keywords: Transverse momentum; Charged particles; Pb–Pb collisions; https://purl.org/pe-repo/ocde/ford#1.03.03